Extraction and characterization of astaxanthin from marine sources - Jaswir, Irwandi; Azfar, Shazana; Amid, Azura (IIUM Press, 2011)
A study has been conducted to extract and to characterizecarotenoid astaxanthin from tiger shrimp (Penaeus monodon). one of most commercial marine sources in Malaysia. Astaxanthin is a red pigment belonging to the family of the xanthophylls, the oxygenated derivatives of carotenoids and is widely used as a pigmentation sources in aquaculture and poultry industries, nutraceutical and pharmaceutical industries. Results showed the carotenoid yield for all combinations of extraction condition ranged from 65-138 J.!g!g. The optimum solvent to waste ratio and the percentage of hexane in solvent mixtures were 1:5.553 and 32.105% which gave the highest yield of ]41.474 j.!g/g. The percentage purity of the astaxanthin (predicted as 13-cisastaxanthin monoester) was about 86.907%. Astaxanthin, astaxanthin monoester, astaxanthin diester,a-carotene are the major pigments in Penaeus monodon.